Association between cardiac autonomic regulation, visceral adipose tissue, cardiorespiratory fitness and ambient air pollution: 4HAIE study (Program-4) - Dostal, Tomas; Dankova, Martina; Barot, Tomas; Sindler, Dominik; Kutac, Petr; Jandackova, Vera; Jandacka, Daniel; Hofmann, Peter; Cipryan, Lukas (PloS one, 2024)
BACKGROUND: The main objective of the present cross-sectional cohort study was to determine whether there is an association between cardiac autonomic regulation, as expressed through heart rate variability (HRV), and cardiorespiratory fitness (CRF), visceral adipose tissue (VAT), and over the long-term living in areas with low or high air pollution. METHODS: The study sample included 1036 (487 females) healthy runners (603) and inactive participants (age 18-65 years) who had lived for at least 5 years in an area with high (Moravian-Silesian; MS) or low (South Bohemian; SB) air pollution in the Czech Republic. A multivariable regression analysis was used to evaluate the associations between multiple independent variables (CRF (peak oxygen consumption), VAT, sex, socioeconomic status (education level), and region (MS region vs. SB region) with dependent variable HRV. The root mean square of successive RR interval differences (rMSSD) was employed for the evaluation of HRV. RESULTS: The multivariable linear regression model revealed that cardiac autonomic regulation (rMSSD) was significantly associated with CRF level (p < .001) and age (p < .001). There were no associations between rMSSD and region (high or low air-pollution), sex, education level or VAT (p > 0.050). CONCLUSIONS: We showed that living in an area with low or high air pollution is not associated with cardiac autonomic modulation in healthy runners and inactive individuals. CRF and age significantly directly and inversely, respectively, associated with HRV. There were no other significant associations.
Keywords: dospělí; autonomní nervový systém; srdce; Cross-Sectional Studies; Humans; lidé středního věku; Intra-Abdominal Fat; Middle Aged; Young Adult; mladý dospělý; Czech Republic; znečištění ovzduší; nitrobřišní tuk; mužské pohlaví; Česká republika; Air Pollution; Autonomic Nervous System; Adult; Heart; průřezové studie; Adolescent; Cardiorespiratory Fitness; ženské pohlaví; Heart Rate; lidé; mladiství; srdeční frekvence; Aged; senioři; kardiorespirační zdatnost; Male; Female